Epigenetic regulation of IncRNA KCNKI5-ASI in gastric cancer - Zhang H; Zhang Z; Wang D (Cancer Management and Research, 2019)
Haiyan Zhang,1 Zhuo Zhang,2 Dayu Wang1 1Department of Gastrointestinal Colorectal and Anal Surgery, China-Japan Union Hospital of Jilin University, Changchun, Jilin, China; 2Department of Urology, China-Japan Union Hospital of Jilin University, Changchun, Jilin, ChinaCorrespondence: Dayu WangDepartment of Gastrointestinal Colorectal and Anal Surgery, China-Japan Union Hospital of Jilin University, No. 126, Xiantai Street, Changchun, Changchun 130033, ChinaEmail lzyhdhbsjz@126.comBackground: Long noncoding RNAs (lncRNAs) play an important role in gastric cancer. In this study, we aimed to uncover the epigenetic regulatory mechanism of lncRNA KCNK15-AS1 in gastric cancer progression.Patients and methods: Forty patients were included in the study. The expression of KCNK15-AS1 was detected by real-time PCR (RT-PCR), the promoter of KCNK15-AS1 was detected by methylation-specific PCR, and the luciferase assay was performed to detect the relationship between KCNK15-AS1 and miR-21. The relationship of the proteins was explored by an RNA pull-down assay and RNA immunoprecipitation. Chromatin immunoprecipitation was performed to detect the relationship between the promoter and the protein.Results: The expression of KCNK15-AS1 was lower in the tumor tissue compared to the normal tissue. KCNK15-AS1 interacted with miR-21. Both the overexpression of KCNK15-AS1 and the knockdown of the expression of miR-21 inhibited proliferation and promoted apoptosis and decreased the level of MMP-9, bcl-2, and MMP-2 but increased the level of Bax. In addition, the methylation of KCNK15-AS1 was detected in the tumor tissue but was not detected in the normal tissue. Treatment with 5-azacytidine and chidamide decreased the level of DNMT1 and HDAC1 and increased the level of KCNK15-AS1. The RNA pull-down and RNA immunoprecipitation results showed that KCNK15-AS1 interacted with DNMT1 and HDAC1. The ChIP-seq result showed that the promoter of MAPK interacted with DNMT1, and the promoter of AKT and STAT5 interacted with HDAC1.Conclusion: In this study, we identified two regulatory axes, namely KCNK15-AS1-DNMT1-MAPK and KCNK15-AS1-HDAC1-AKT, which were associated with gastric cancer progression. Chidamide and 5-azacytidine might provide new modes for treating gastric cancer.Keywords: lncRNA, KCNK15-AS1, DNMT1, HDAC1, gastric cancer, miR-21